Analysis of the Determinants of Non-Performing Financing (NPF) at Sharia Commercial Banks in Indonesia - Deris Lazuardi; Muhammad Aswad; Rokhmat Subagiyo (LABATILA : Jurnal Ilmu Ekonomi Islam, 2026)
Sharia banking plays a strategic role in supporting national development to promote the distribution of prosperity among the people. This study aims to examine and analyze the influence of the Capital Adequacy Ratio (CAR), Return on Assets (ROA), and Operating Expenses to Operating Income (OEOI/BOPO) on Non-Performing Financing (NPF) at Sharia Commercial Banks in Indonesia in the 2021-2025 period, both partially and simultaneously. Using the Agency Theory perspective, this study evaluates the performance of management (the agent) in managing funds (the principal) to mitigate risk. The research approach is quantitative, utilizing secondary data sourced from the official annual reports of each bank. The analysis technique employed is panel data regression using the Common Effect Model (CEM), processed using RStudio software version 2026. The research sample consists of five sharia commercial banks selected through purposive sampling. The results show that, when analyzed partially, CAR has no influence on NPF, while ROA and OEOI/BOPO have a positive and significant influence on NPF. Simultaneously, CAR, ROA, and OEOI/BOPO have a significant influence on NPF, with an R-squared (R2) value of 0.6831 and an adjusted R-squared of 0.6340, indicating that 63.40% of the variation in NPF can be explained by the model. The study’s conclusion confirms that operational inefficiencies and risk-taking behavior by management in pursuit of profitability are the primary determinants that increase the risk of non-performing loans. Therefore, sharia banking management is expected to strengthen internal oversight and apply the principle of prudence to maintain the long-term stability of asset quality.